2011
DOI: 10.5430/ijba.v2n1p98
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Business Students’ Perceptions of Service Quality Offered in Kenyan Universities

Abstract: The purpose of this study was to ascertain business students' perception of quality of service provided by public and private universities in Kenya. As a comparative study, it aimed at understanding how various factors or dimensions of service quality affected their perception within a university setting. The comparison was between two public and two private universities located in rural and urban settings in Kenya. A survey design of cross sectional nature was used to assess business students' perception of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 29 publications
(28 reference statements)
1
26
1
1
Order By: Relevance
“…Arguably, HEdPERF instrument "has the advantage of being more specific in the area of higher education sector" (Kimani et al, 2011). The HEdPERF instrument, as provided by Brochado (2009) was initially used.…”
Section: Aim and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Arguably, HEdPERF instrument "has the advantage of being more specific in the area of higher education sector" (Kimani et al, 2011). The HEdPERF instrument, as provided by Brochado (2009) was initially used.…”
Section: Aim and Methodologymentioning
confidence: 99%
“…Thus, the question "The hostel facilities and equipment are adequate and necessary" was changed into C10: "Restaurant and other food services, facilities and equipment are adequate and convenient". Recent studies (Wibisono and Nainggolan, 2009;Legcevic, 2010;Kimani et al, 2011;Ravichandran et al, 2012) showed that factor loadings of the proposed HEdPERF original dimensions differ significantly when HEdPERF is used in the context of higher education sectors other than Malaysia, implying that certain modifications can be made. The dimensions and their items of the modified HEdPERF can be found in the Appendix.…”
Section: Aim and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…In consequence, unless they manage to gain a correct understanding of the expectations and requirements of their customers, they are bound to fail. Only little researches have been conducted so far on the perception level of students with regard to service quality (Kimani, Kagira et al 2011). On the other hand, the researches done in developing countries regarding the students" perception on service quality are generally focus on the students in private institutions and universities and not the ones in public universities.…”
Section: Introductionmentioning
confidence: 99%